THE EFFECT OF STRATEGIC PLANNING AND PERFORMANCE MANAGEMENT ON BUSINESS AND PRODUCTION PROCESS - Juninetenth Keeply F. Sitanggang (Program Studi Magister Manajemen Universitas Advent Indonesia, 2018)
A business process is a set of activities that designed to produce an output for aparticular customer or market. It’s emphasis on how the work within an organization, in contrastto a product's focus on what a process is. Thus the specific sequence of work activities in all timesand places, with the beginning, end, and input, output, and structure of the action clearly defined.The purpose of this study to determine whether the strategic planning and performancemanagement effect on business and production process on the three universities in SDA amongIndonesia region. This research uses the questionnaire to collect data and using Pearson productmomentto find the relationship and effect of the variable. The result shows that the correlationamong at variables was having a significant relationship between strategic planning, and businessproduction process with the coefficient correlation of 0.720 that mean the correlation was strong.Performance management on a business production process coefficient correlation of 0.780 thatmean the correlation was strongly positive and the relationship between variables strategicplanning, and performance management on business production process was 0.823 strongpositive. The contribution of these two variables strategic planning and performance managementon business and production process was 67,7% and the rest 32,3% determined by other variablesor factor's out of this research. Also, there is a relationship between strategic planning andperformance management to business and production process with f Value of 169.813. Theregression equation is BP = 0.583 + 0.361SP + 0.481PM.